PERBANDINGAN MATERIAL AKUSTIK DALAM MENYERAP BUNYI - Mohamad Fikri Datuela; Rahmayanti Rahmayanti; Wahyu Saputra; Nur Mutmainnah; Syafriani Syafriani (JAMBURA Journal of Architecture, 2023)
This study aims to examine the comparison of room acoustics by using room engineering methods and testing zinc plate and GRC board materials in the same room. The results of the study show that the selection of materials for sound absorption in the room must be considered carefully and adjusted to the desired sound absorption needs. In testing using the room engineering method, it was seen that there was an increase in the effectiveness of sound absorption in both materials at various volume levels. However, in testing using the mandatory sound of the room acoustic tester, it can be seen that the sound frequency at the lower speaker position is more prominent in both materials at a lower volume. Meanwhile, in the test using the free sound of people giving speeches, it was seen that there was an increase in sound frequency at the top speaker position for both materials at a higher volume.